Characterization of Postharvest Practices and Losses of Fresh Produce along the Caribbean Supply Chain: Guyana and St. Kitts-Nevis - Cortbaoui , Patrick E; Ngadi, Michael O (Journal of Postharvest Technology, 2016)
Inefficient handling and high postharvest losses describe the Caribbean supply chain of fresh fruits and vegetables. In this study, two different approaches to characterize the postharvest practices and losses of key agricultural commodities (tomato, string beans, eggplant, okra and cucumber) were developed for Guyana and St. Kitts-Nevis: (1) producer household surveys (PHS) and (2) modified count and weight (MCW). Results from the PHS baseline surveys revealed that Caribbean farmers sell most of their harvested crops to local markets, keeping the remaining crops for household consumption. In Guyana, the majority of farmers (97%) reported selling their crops at harvest, while in St. Kitts-Nevis, 61% of farmers stored their produces before selling. One plausible explanation for this practice is that farmers delay selling to obtain higher prices based on market demands. While farmers in St. Kitts-Nevis reported 30% postharvest losses of crops due to spoilage, those in Guyana reported considerably less. Results from modified count and weight method revealed that small producers experienced greater postharvest loss compared to large ones due to spoilage and lack of market access. A reasonable explanation to this is the degree of knowledge in high-value crop production between the two types of farmers. As the produce travelled throughout the supply chain, it started to lose significantly (P < 0.05) its freshness and its marketable value as well. At the marketing level, small and large retailers in both countries experienced substantial postharvest quantitative and qualitative losses. These losses were due to inappropriate handling and exposure to undesirable environmental conditions.